A high molecular weight polymer thickener and its synthesis method and application
Through a synthesis method of polymer thickening agent, the problem of poor stability of fracturing liquid thickening agent under high temperature conditions is solved, and the effects of high viscosity, shear resistance and salt resistance are achieved, which is suitable for improving the Thickening and sand carrying capacity of fracturing fluid.
Patent Information
- Application Number
- CN202411658139.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing fracturing liquid thickening agent has poor stability under high temperature conditions, resulting in a decrease in viscosity and losing the role of thickening, sand carrying, and seam formation. At the same time, there are problems of insufficient shear resistance and salt resistance and hardness resistance.
Using a polymer thickening agent, the synthesis method includes sequential addition of 4-trifluoromethylcinnamic acid, hydroxyethyl cellulose, TX-10, potassium dihydrogen phosphate in the reactor, and drops through the initiator Add, stirring and insulation reactions continuously to form a ternary polymer thickening agent with linear structure and crosslinking ability.
The synthesis of polymer thickeners has been achieved, with high apparent viscosity, good shear resistance and salt and hardness resistance, and can remain stable under high temperature conditions. It is suitable for thickening and sand carrying of fracturing fluids. .
Smart Images

Figure 9RIFOJRNMK3LKOBS5M0OBGVOUAPQOZALOJXGXM11 
Figure LHQYYWCJ1KNJ8JMH7E5ZGITF7QDGYNEA8OHOUQ35 
Figure LKTAXYW5DMEWOV7SSXTFQJDEUKE7E4ORFPXA64DR
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of petroleum extraction, and in particular relates to a high molecular polymer thickener and a synthesis method and application thereof. Background Art
[0002] Fracturing technology is a conventional production-increasing technology. Its purpose is to press cracks into the reservoir, thereby increasing production. The fracturing fluid used in fracturing must have the characteristics of high viscosity, high shear resistance, high sand carrying capacity, and environmental protection without residue after gel breaking. High viscosity facilitates the formation of cracks, and only high viscosity can make the cracks reach the required width and depth. As the main agent of water-based fracturing fluid, thickener is used to increase the viscosity of fracturing fluid, reduce fracturing fluid filtration, and suspend and carry proppants. At present, the thickeners used in water-based fracturing fluid are mainly natural plant gums and their derivatives, among which hydroxypropyl guar gum is the most used. They have the characteristics of mature technology, stable colloids and sufficient supply. However, it is reported that the commonly used guar gum fracturing fluid system will not only form filter cakes on the surface of the cracks, but also leave some residues in the formation and cracks, causing secondary damage.
[0003] Compared with natural plant gums and their derivatives and cellulose and its derivatives, artificial synthetic polymers have better viscosity-temperature characteristics and high-temperature stability, and have the advantages of being insensitive to bacteria, good stability, and strong sand-carrying capacity. General synthetic polymers include polyacrylamide, methylene polyacrylamide, etc. These polymers can be controlled by controlling the synthesis conditions to change the polymer properties to meet the construction needs. They have good resistance reduction performance, but the problem is the disadvantage of poor shear resistance. Oligomer fracturing fluid makes up for the shortcomings of the above polymers, but oligomers are not able to withstand high temperatures. They hydrolyze and break chains under high temperature conditions, losing the functions of fracturing for thickening, carrying sand, and creating seams.
[0004] CN91111287.1 discloses a method for preparing a fracturing fluid thickener, which is suitable for fracturing and transformation operations of low permeability oil and gas layers. The thickener is made of plant radix tenuifolia powder, which is chemically modified by ethanol, caustic soda, propylene oxide and water. Its water-insoluble matter is significantly lower than that of the plant radix tenuifolia thickener currently used in fracturing fluids, so it causes little damage to the formation and can achieve a production increase effect. However, compared with synthetic polymer thickeners, the fracturing fluid thickener contains a high amount of residue and has poor temperature resistance.
[0005] CN201911175892.8 discloses a high temperature resistant thickener for fracturing fluid and its preparation method and application, including a high temperature resistant thickener for fracturing fluid, the thickener includes acrylamide, salt resistant functional monomer and thermosensitive functional monomer free radical; the molar ratio of acrylamide, salt resistant functional monomer and thermosensitive functional monomer is 1: (0.01-0.08): (0.05-0.15). The invention introduces thermosensitive units and salt resistant units into the acrylamide molecular chain by solution copolymerization, giving the copolymer excellent high temperature resistance and salt resistance, and at the same time having good solubility, viscoelasticity and sand carrying capacity. However, since it does not actually solve the problem of cross-linking bond breakage of the fracturing fluid thickener at high temperature, the stability of the fracturing fluid thickener is poor. Summary of the invention
[0006] The present invention aims at the deficiencies of the above-mentioned prior art and provides a high molecular polymer thickener and its preparation method and application. The present invention has the advantages of simple synthesis, high apparent viscosity, strong shear resistance, and good salt resistance and hardness resistance.
[0007] In order to achieve the above object, in the first aspect, the present invention discloses a method for synthesizing a high molecular weight polymer thickener, and the specific steps of the synthesis method are as follows:
[0008] (1) Purge the first reactor and pipeline with nitrogen, add 4-trifluoromethylcinnamic acid, deionized water, hydroxyethyl cellulose, TX-10, and potassium dihydrogen phosphate into the reactor in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;
[0009] (2) Add 4,4'-diaminobenzylbenzene-2,2'-disulfonic acid, 2-allyloxymethyl-2-hydroxymethylpropane-1,3-diol and deionized water to the second reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;
[0010] (3) Add the initiator to the high-position drop-adding tank, drip it into the first reactor, and stir continuously. When the viscosity begins to rise, add the mixed liquid in the second reactor, continue stirring for 20-30 minutes, then raise the temperature to 55-60°C, keep the temperature for 60-120 minutes, and obtain a viscous liquid;
[0011] (4) Drying and granulating the viscous liquid to obtain a product thickener.
[0012] In the present invention, preferably, the molar ratio of 4,4'-diaminostilbene-2,2'-disulfonic acid, 2-allyloxymethyl-2-hydroxymethylpropane-1,3-diol and 4-trifluoromethylcinnamic acid is 0.2-0.4:0.5-1:1.
[0013] In the present invention, preferably, in step (1), the weight ratio of deionized water, hydroxyethyl cellulose, TX-10, potassium dihydrogen phosphate and 4-trifluoromethylcinnamic acid is 4-6: 0.05-0.1: 0.05-0.1: 0.02-0.05: 1.
[0014] In the present invention, preferably, in step (2), the weight ratio of deionized water to 4-trifluoromethylcinnamic acid is 2-3:1.
[0015] In the present invention, preferably, in step (3), the initiator is a mixed solution of persulfate and sodium bisulfite, wherein the concentration of persulfate is 10-12wt%, the concentration of sodium bisulfite is 4-6wt%, and the weight ratio of the initiator to 4-trifluoromethylcinnamic acid is 0.2-0.4:1.
[0016] Preferably, the persulfate is one of potassium persulfate, ammonium persulfate and sodium persulfate.
[0017] The synthetic reaction equation of the polymer thickener of the present invention is as follows:
[0018]
[0019]
[0020] In a second aspect, the present invention discloses a polymer thickener, the molecular structure of which is as follows:
[0021]
[0022] in:
[0023] x=10000-100000;
[0024] y=2000-40000;
[0025] z=5000-100000.
[0026] Preferably, the viscosity average molecular weight of the high molecular weight polymer thickener is 10,000,000-15,000,000.
[0027] In a third aspect, the present invention discloses the use of the above-mentioned high molecular polymer thickener in fracturing fluid.
[0028] The polymer thickener of the present invention is a ternary polymer. The polymerized monomers include 4-trifluoromethylcinnamic acid, 4,4'-diaminostilbene-2,2'-disulfonic acid, and 2-allyloxymethyl-2-hydroxymethylpropane-1,3-diol, and the molecule has a linear structure. The molecule contains amino and hydroxyl groups, which can be cross-linked with various cross-linking agents such as boron, zirconium, and titanium to form two-dimensional and three-dimensional structures, greatly improving its viscosity; the molecule contains fluorocarbon lipophilic groups, and the molecule contains carboxyl and sulfonic acid hydrophilic groups, which can reduce surface interfacial tension and reduce friction resistance during the migration of fracturing fluid; the molecule contains a benzene ring structure, which can increase shear resistance; hydroxyethyl cellulose plays the role of a dispersant in the polymerization process, which can improve the polymerization effect of the present invention and also enhance the cross-linking effect.
[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0030] (1) The polymer thickener of the present invention is synthesized by a one-pot method, the synthesis process is simple, and there are no by-products;
[0031] (2) The polymer thickener of the present invention has a relatively high apparent viscosity, and the viscosity reaches 105 mPa•s or above when the concentration is 2000 mg / L;
[0032] (3) The polymer thickener of the present invention has good shear resistance and can withstand high temperatures at 170S. -1 Under the condition of continuous shearing for 120 minutes, the viscosity retention rate reached more than 90%;
[0033] (4) The polymer thickener of the present invention has good salt resistance and hardness resistance. When the polymer thickener contains 50,000 mg / L salt and is prepared with simulated formation water containing 10,000 mg / L hardness to a concentration of 2,000 mg / L, the viscosity reaches more than 100 mPa•s. DETAILED DESCRIPTION
[0034] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0035] The technical solution of the present invention is further described below in conjunction with specific embodiments:
[0036] Example 1
[0037] (1) Purge the first reactor and pipeline with nitrogen, add 0.1 mol 4-trifluoromethylcinnamic acid, 86.4 g deionized water, 1.08 g hydroxyethyl cellulose, 1.08 g TX-10, and 0.43 g potassium dihydrogen phosphate into the reactor in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;
[0038] (2) Add 0.02 mol of 4,4'-diaminobenzylbenzene-2,2'-disulfonic acid, 0.1 mol of 2-allyloxymethyl-2-hydroxymethylpropane-1,3-diol, and 43.2 g of deionized water to the second reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;
[0039] (3) 8.64 g of initiator was added to the high-position dropping tank. The initiator was a mixture of 10 wt% potassium persulfate and 4 wt% sodium bisulfite. The mixture was added dropwise to the first reactor and stirred continuously. When the viscosity began to rise, the mixed liquid in the first reactor was added and stirred for 30 min. The temperature was then raised to 55 °C and kept for 120 min to obtain a viscous liquid.
[0040] (4) Drying and granulating the viscous liquid to obtain a product thickener.
[0041] Example 2
[0042] (1) Purge the first reactor and pipeline with nitrogen, add 0.1 mol 4-trifluoromethylcinnamic acid, 92.8 g deionized water, 1.47 g hydroxyethyl cellulose, 1.14 g TX-10, and 0.68 g potassium dihydrogen phosphate into the reactor in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;
[0043] (2) Add 0.025 mol 4,4'-diaminobenzylbenzene-2,2'-disulfonic acid, 0.09 mol 2-allyloxymethyl-2-hydroxymethylpropane-1,3-diol, and 47.2 g deionized water to the second reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;
[0044] (3) 7.32 g of initiator was added to the high-position dropping tank. The initiator was a mixture of 11 wt% potassium persulfate and 4 wt% sodium bisulfite. The mixture was added dropwise to the first reactor and stirred continuously. When the viscosity began to rise, the mixed liquid in the first reactor was added and stirred for 20 min. The temperature was then raised to 58 °C and kept for 90 min to obtain a viscous liquid.
[0045] (4) Drying and granulating the viscous liquid to obtain a product thickener.
[0046] Example 3
[0047] (1) Purge the first reactor and pipeline with nitrogen, add 0.1 mol 4-trifluoromethylcinnamic acid, 100.7 g deionized water, 1.66 g hydroxyethyl cellulose, 1.88 g TX-10, and 0.92 g potassium dihydrogen phosphate into the reactor in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;
[0048] (2) Add 0.03 mol of 4,4'-diaminobenzylbenzene-2,2'-disulfonic acid, 0.08 mol of 2-allyloxymethyl-2-hydroxymethylpropane-1,3-diol, and 53 g of deionized water to the second reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;
[0049] (3) Add 6.44 g of initiator, which is a mixture of 11 wt% sodium persulfate and 5 wt% sodium bisulfite, to the high-position dropping tank, and drip it into the first reactor. Stir continuously. When the viscosity begins to rise, add the mixed liquid in the first reactor. Continue stirring for 25 min. Then raise the temperature to 60 ° C. and keep the temperature for 60 min to obtain a viscous liquid.
[0050] (4) Drying and granulating the viscous liquid to obtain a product thickener.
[0051] Example 4
[0052] (1) Purge the first reactor and pipeline with nitrogen, add 0.1 mol 4-trifluoromethylcinnamic acid, 114.7 g deionized water, 1.92 g hydroxyethyl cellulose, 2.16 g TX-10, and 1.08 g potassium dihydrogen phosphate into the reactor in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;
[0053] (2) Add 0.035 mol 4,4'-diaminobenzylbenzene-2,2'-disulfonic acid, 0.07 mol 2-allyloxymethyl-2-hydroxymethylpropane-1,3-diol, and 64.8 g deionized water to the second reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;
[0054] (3) Add 5.14 g of initiator, which is a mixture of 12 wt% sodium persulfate and 5 wt% sodium bisulfite, to the high-position dropping tank, and drip it into the first reactor. Stir continuously. When the viscosity begins to rise, add the mixed liquid in the first reactor. Continue stirring for 22 min. Then raise the temperature to 58 °C and keep the temperature for 100 min to obtain a viscous liquid.
[0055] (4) Drying and granulating the viscous liquid to obtain a product thickener.
[0056] Example 5
[0057] (1) Purge the first reactor and pipeline with nitrogen, add 0.1 mol 4-trifluoromethylcinnamic acid, 129.6 g deionized water, 2.16 g hydroxyethyl cellulose, 1.68 g TX-10, and 1.03 g potassium dihydrogen phosphate into the reactor in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;
[0058] (2) Add 0.04 mol of 4,4'-diaminobenzylbenzene-2,2'-disulfonic acid, 0.05 mol of 2-allyloxymethyl-2-hydroxymethylpropane-1,3-diol, and 61 g of deionized water to the second reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;
[0059] (3) 4.32 g of initiator was added to the high-position dropping tank. The initiator was a mixture of 12 wt% ammonium persulfate and 6 wt% sodium bisulfite. The mixture was added dropwise to the first reactor and stirred continuously. When the viscosity began to rise, the mixed liquid in the first reactor was added and stirred for 27 min. The temperature was then raised to 60 °C and kept for 88 min to obtain a viscous liquid.
[0060] (4) Drying and granulating the viscous liquid to obtain a product thickener.
[0061] Example 6
[0062] (1) Purge the first reactor and pipeline with nitrogen, add 0.1 mol 4-trifluoromethylcinnamic acid, 104.6 g deionized water, 2.1 g hydroxyethyl cellulose, 1.98 g TX-10, and 0.83 g potassium dihydrogen phosphate into the reactor in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;
[0063] (2) Add 0.03 mol of 4,4'-diaminobenzylbenzene-2,2'-disulfonic acid, 0.06 mol of 2-allyloxymethyl-2-hydroxymethylpropane-1,3-diol, and 56.4 g of deionized water to the second reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;
[0064] (3) 4.64 g of initiator, which is a mixture of 12 wt% ammonium persulfate and 5 wt% sodium bisulfite, is added to the high-position dropping tank and added dropwise to the first reactor with continuous stirring. When the viscosity begins to rise, the mixed liquid in the first reactor is added and stirred for 30 min. The temperature is then raised to 59 °C and the mixture is kept warm for 120 min to obtain a viscous liquid.
[0065] (4) Drying and granulating the viscous liquid to obtain a product thickener.
[0066] Example 7 Test of apparent viscosity
[0067] The polymer thickener of the present invention (Example 1-6) was prepared into a solution with a concentration of 2000 mg / L with deionized water and heated at 60°C and 170S -1 Under the condition of , the apparent viscosity μ is tested by DV-III Brookfield viscosity test. 0 .
[0068] The acid fracturing fluid of Henan Daochun New Material Technology Co., Ltd. was used as a comparison sample, and the test results are shown in Table 1.
[0069] It can be seen from Table 1 that the high molecular polymer thickener of the present invention (Examples 1-6) has a relatively high apparent viscosity. When the concentration is 2000 mg / L, the viscosity reaches 105 mPa•s and above, and the highest reaches 124 mPa•s (Example 5). The apparent viscosity of the acid fracturing fluid of the comparative example Henan Daochun New Material Technology Co., Ltd. is 40 mPa•s, which is significantly lower than that of the present invention.
[0070] Example 8 Shear resistance test
[0071] The solution of Example 7 was heated at 60°C and 170S - Under the condition of continuous shearing for 120 minutes, the apparent viscosity μ 1 .
[0072] The shear resistance is denoted as η,
[0073] η=μ 1 / μ 0 × 100%
[0074] The acid fracturing fluid of Henan Daochun New Material Technology Co., Ltd. was used as a comparison sample, and the test results are shown in Table 1.
[0075] It can be seen from Table 1 that the polymer thickener of the present invention (Examples 1-6) has good shear resistance. -1 Under the conditions of continuous shearing for 120 minutes, the viscosity retention rate reached more than 90%, with the highest reaching 91.1% (Example 4); while the viscosity retention rate of the acid fracturing fluid of the comparative example Henan Daochun New Material Technology Co., Ltd. was more than 60%, which was significantly lower than that of the present invention.
[0076] Example 9 Salt resistance and hardness resistance test
[0077] Prepare simulated water: Add sodium chloride and calcium chloride to water to prepare simulated formation water with a salt content of 50,000 mg / L and a hardness of 10,000 mg / L.
[0078] The simulated water of the present invention was used to prepare a solution with a concentration of 2000 mg / L and heated at 60°C and 170S -1Under the condition of , the apparent viscosity μ is tested by DV-III Brookfield viscosity test. 2 .
[0079] The acid fracturing fluid of Henan Daochun New Material Technology Co., Ltd. was used as a comparison sample, and the test results are shown in Table 1.
[0080] Table 1 Test results of apparent viscosity, shear resistance, salt resistance and hardness resistance
[0081] μ0, mPa•s η,% μ2, mPa•s Example 1 105 90.2 102 Example 2 118 90.3 106 Example 3 118 90.5 105 Example 4 122 91.1 109 Example 5 124 91 110 Example 6 121 90.6 108 Comparative Example 40 60 28
[0082] It can be seen from Table 1 that the high molecular polymer thickener of the present invention (Examples 1-6) has good salt resistance and hardness resistance. It contains 50,000 mg / L salt and is configured with a concentration of 2,000 mg / L using simulated formation water containing 10,000 mg / L hardness. The viscosity reaches above 100 mPa•s, and the highest reaches 110 mPa•s (Example 5). The viscosity of the acid fracturing fluid of the comparative example Henan Daochun New Material Technology Co., Ltd. is 28 mPa•s, which is significantly lower than that of the present invention.
[0083] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0084] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0085] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for synthesizing a high molecular weight polymer thickener, characterized in that: The specific steps of the synthetic method are as follows: (1) Purge the first reactor and pipeline with nitrogen, add 4-trifluoromethylcinnamic acid, deionized water, hydroxyethyl cellulose, TX-10, and potassium dihydrogen phosphate into the reactor in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution; (2) Add 4,4'-diaminobenzylbenzene-2,2'-disulfonic acid, 2-allyloxymethyl-2-hydroxymethylpropane-1,3-diol and deionized water to the second reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution; (3) Add the initiator to the high-position drop-adding tank, drip it into the first reactor, and stir continuously. When the viscosity begins to rise, add the mixed liquid in the second reactor, continue stirring for 20-30 minutes, then raise the temperature to 55-60°C, keep the temperature for 60-120 minutes, and obtain a viscous liquid; (4) drying and granulating the viscous liquid to obtain a product thickener; The molar ratio of 4,4'-diaminostilbene-2,2'-disulfonic acid, 2-allyloxymethyl-2-hydroxymethylpropane-1,3-diol and 4-trifluoromethylcinnamic acid is 0.2-0.4:0.5-1:1; The molecular structure of the thickener is as follows: in: x=10000-100000; y=2000-40000; z=5000-100000。 2. The synthesis method according to claim 1, characterized in that: In step (1), the weight ratio of deionized water, hydroxyethyl cellulose, TX-10, potassium dihydrogen phosphate and 4-trifluoromethylcinnamic acid is 4-6: 0.05-0.1:0.05-0.1:0.02-0.05:1。 3. The synthesis method according to claim 1, characterized in that: In step (2), the weight ratio of deionized water to 4-trifluoromethylcinnamic acid is 2-3:
1.
4. The synthesis method according to claim 1, characterized in that: In step (3), the initiator is a mixed solution of persulfate and sodium bisulfite, wherein the concentration of persulfate is 10-12wt%, the concentration of sodium bisulfite is 4-6wt%, and the weight ratio of the initiator to 4-trifluoromethylcinnamic acid is 0.2-0.4:
1.
5. The synthesis method according to claim 4, characterized in that: The persulfate is one of potassium persulfate, ammonium persulfate and sodium persulfate.
6. The high molecular weight polymer thickener prepared by the synthesis method according to any one of claims 1 to 5, characterized in that: The molecular structure of the polymer thickener is as follows: in: x=10000-100000; y=2000-40000; z=5000-100000。 7. The high molecular polymer thickener according to claim 6, characterized in that: The viscosity average molecular weight of the high molecular polymer thickener is 10,000,000-15,000,000.
8. Use of the high molecular polymer thickener according to claim 6 or 7 in fracturing fluid.
Citation Information
Patent Citations
High-temperature-resistant thickening agent for fracturing fluid, and preparation method and application thereof
CN111019042A
Acid solution thickening agent and preparation method thereof
CN116693744A
Temperature-resistant and salt-resistant polyacrylamide for oil displacement and synthesis method of temperature-resistant and salt-resistant polyacrylamide
CN117866141A